Increased menopausal symptoms among Afro-Colombian Women as assessed with the menopause rating scale. (2008)
Increased frequency and severity of menopausal symptoms have been associated to black race. However, this situation has not been described in any Latin American population. Objective: Compare frequency and severity of menopausal symptoms among Afro and non-Afro Hispanic Colombian climacteric women. Methods: In this cross-sectional study, healthy Afro and non-Afro-Colombian women aged 40–59 years were asked to fill out the Menopause Rating Scale (MRS) questionnaire in order to compare symptom frequency and intensity. Results: A total of 578 women were surveyed (201 Afro-Colombian and 377 non-Afro-Colombian). Mean age of the whole sample was 47.9 ± 5.9 years (median 47), with no differences among studied groups in terms of age, parity, and hormone therapy (HT) use. Intensity of menopausal symptoms, assessed with the total MRS score, was found to be significantly higher among Afro-Colombian women (10.6 ± 6.7 vs. 7.5 ± 5.7, p = 0.0001), which was due to higher somatic and psychological subscale scores. In this group, the frequency of somatic symptoms, heart discomfort and muscle and joint problems, was found to be higher than in non-Afro-Colombian women (38.8% vs. 26.8% and 77.1% vs. 43.5%, respectively, p < 0.05); equally, all items of the psychological subscale (depressive mood, irritability, anxiety and physical exhaustion) were also found to be higher among black women. On the other hand, compared to black women non-Afro-Colombian ones presented more bladder problems (24.9% vs. 14.9%, p = 0.005). After adjusting for confounding factors, logistic regression analysis determined that black race increased the risk for presenting higher total MRS scorings (OR: 2.31; CI 95%: 1.55–3.45, p = 0.0001).